Microbial Community Compositions and Geochemistry of Sediments with Increasing Distance to the Hydrothermal Vent Outlet in the Kairei Field. Issue 3 (15th March 2020) - Adam, Nicole; Kriete, Cornelia; Garbe-Schönberg, Dieter; Gonnella, Giorgio; Krause, Stefan; Schippers, Axel; Kurtz, Stefan; Schwarz-Schampera, Ulrich; Han, Yuchen; Indenbirken, Daniela; Perner, Mirjam
Abstract: Microbial metabolisms in sediments play a pivotal role in marine element cycling. In hydrothermal sediments chemosynthetic microorganisms likely prevail, while in non-hydrothermally impacted sediment regimes microorganisms associated with organic matter decomposition are primarily recognized. To test how these microorganisms are distributed along the hitherto neglected transition zone influenced to different degrees by hydrothermal input we sampled four sediment sites: these were (i) near an active vent, (ii) the outer rim, and (iii) the inactive area of the Kairei hydrothermal field as well as (iv) sediments roughly 200 km south-east of the Kairei field. Chemistry and microbial community compositions were different at all sampling sites. Against expectations, the sediments near the active vent did not host typical chemosynthetic microorganisms and chemistry did not indicate current, extensive hydrothermal venting. Data from the outer rim area of the active Kairei field suggested microbially mediated saponite production and diffuse hydrothermal flow from below accompanied by increased metal concentrations. A steep redox gradient in the inactive Kairei field points towards significant redox driven processes resulting in dissolution of hydrothermal precipitates and intense metal mobilization. Local microorganisms were primarily Chloroflexi, Bacillales, Thermoplasmata, and Thaumarchaeota .